TRUE LOVE OF HABIBIE AND AINUN IN BACHARUDDIN JUSUF HABIBIE’S NOVEL HABIBIE AND AINUN - ADE ROSA ARIANTI NASUTION (LP2MTBM MAKARIOZ, 2021)
This thesis is the result of a research on true love depicted from a autobiographical novel Habibie and Ainun written byBacharuddin Jusuf Habibie in 2010. There are only two characters Habibie and Ainun. The story is derived from the author‟sreal life. Face condition after the departure of Habibie‟s wife. The true love is their goal relationship. The objective is to findout the indicators of true love reflected through the characters of the novel Habibie and Ainun. And how does true lovedepicted in the novel affect the main characters in the novel Habibie and Ainun, in which Riyanto (2015) states that true loveis when the feeling is connected, attached to someone voluntarily with a happy permanent sense of connection, and itconsists of three indicators : loyalty, tolerance, and perseverance. A character between Habibie and Ainun is a goodcollaboration, Ainun is a great wife and mom, she is loyal, tolerate to her husband, and be a good companion to herhusband. While Habibie has a good attitude, wise, responsible, and also romantic. They always keep the loyalty for eachother, there were Habibie, there was Ainun. And they can make their love relationship be balanced between household andcareer. This research used qualitative method proposed by Miles and Huberman (1994). A main task is to explicate the wayspeople in particular settings, come to understand, account for, take action, and otherwise manage their situation.